Do Immigrants Work in Worse Jobs than U.S. Natives? Evidence from California - Madeline Zavodny (Institute for the Study of Labor (IZA), 2014)
In the debate over immigration reform, it is frequently asserted that immigrants take jobs that U.S. natives do not want. Using data from the 2000 Census merged with O*NET data on occupation characteristics, I show that the jobs held by immigrants are more physically arduous than the jobs held by U.S. natives. However, data from the California Work and Health Survey on self-reported physical job demands indicate that immigrants do not perceive their jobs as requiring more physical effort than U.S. natives. Immigrants thus have worse jobs than natives but do not view them as such.
Keywords: J81; J15; 330; immigrants; working conditions; compensating differentials